"Fit to Enter the World": Hannah Arendt on Politics, Economics, and the Welfare State. Issue 4 (10th October 2014) - KLEIN, STEVEN
<x content-type="archive" xml:space="preserve">Abstract</x> What is the significance of the welfare state and struggles over social and economic needs for democratic politics? This article turns to Hannah Arendt's thought to articulate new possibilities for relating democratic agency and the welfare state, possibilities neglected by currently dominant deliberative and radical democratic approaches. Against critics who claim that Arendt seeks to purify politics of economic and social problems, I argue that she presents a sophisticated account of the vital importance of economic matters for public life. For Arendt, the danger is not the invasion of politics by economics, but rather the loss of the worldly, mediating institutions that allow economic matters to appear as objects of public concern. Reconstructing her account of these mediating institutions, I show that Arendt's analysis opens up novel insights into the relationship between democratic action and welfare institutions, drawing attention to how such institutions transform material necessity into shared objects of attachment, judgment, and action.